Support for Radical Left Ideologies Among Youth in Switzerland - Jacot Cédric; Baier Dirk; Haymoz Sandrine; Isenhardt Anna; Kamenowski Maria; Manzoni Patrik (Swiss Journal of Sociology)
This article aims to better understand the determinants which support the ideologies of the Radical Left among young people in Switzerland. The analyses presented in the article are based on a survey on the theme of political radicalism which has been carried out in secondary schools on level II. The findings showed that economic and political deprivation, as well as a high degree of anti-authoritarianism, increase the probability of adhering to the different ideologies of the Radical Left. They also suggest that several aspects of the school context have an impact on the ideological positioning of young people.